Strategy For Development Of The Kampung Empon-Empon Program In Ngalian Widodomartani Village - Ulhaq, Hanifah Dhiya; Murdiyanto, Eko (Journal of Agricultural Social and Business, 2024)
This study aims to Assess the potential and activities that supports the Ngalian Empon-empon Village and also develop strategies needed for the development of the Empon-empon Kampung Program. This research is a descriptive research with a qualitative approach to the type of case study research. The data sources used are primary data and secondary data. Data collection techniques using interview techniques, observation, and documentation. Data validity using source triangulation. Data analysis techniques use interactive models, namely collecting data, reducing data, presenting data as well as drawing conclusions and verification. The result of this research are The potential that supports the Ngalian empon-empon village program includes physical and non-physical potential. Activities that have been carried out in the Empon-empon Village Program include planting empon-empon by utilizing the land in the yard of the house, planting empon-empon in demonstration plots for each RT and making processed empon-empon in the form of simplicia, pure powder, instant or syrup. The strategy needed for the development of the Empon-empon village program is the establishment of the Ngalian Empon-empon education village.